Effect of Fertilisers on Development of Endomycorrhiza in Kauri Pine (Agathis robusta) - Thapar, H. S.; Khan, S. N.; Ram, M. A. R.; Bakshi, B. K. (Indian Forester, 1984)
The effect of mineral fertilisers and compost on the development of endomycorrhiza in Kauri pine (Agathis robusta C. Moore F.M. Bailey), an exotic species in India, was stUdied. Addition of compost to soil resulted in significant increase in plant growth and resulted in increased Endogone spore population in the substrate. Mineral fertilizer exerted a depressing effect on plant growth and Endogone spore population tven when compost was added to the substrate. Use of compost is therefore recommended in the nursery.